The importance of optimizing the process of ensuring the psychometric criteria of the scientificity of psychodiagnostic methodologies (Acta Education, 2025)
The article highlights one of the current issues for psychology specialists: adapting methodologies to the ethno-cultural environment, or solving problems in the process of providing psychometric criteria in the development of various questionnaires in optimal ways. Solving such problems allows psychologists to master new psychodiagnostic methods based on scientific research. The process of optimizing psychometric criteria allows us to take into account this diversity and adapt methodologies for different cultures. The process of providing psychometric criteria must comply with professional standards, which increases professionalism in the field of psychology.